2011
DOI: 10.1186/1472-6963-11-195
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the implementation of a tool for lifestyle intervention in primary health care: a qualitative study among managers and professional groups

Abstract: BackgroundIn recent years there has been increasing interest in transferring new knowledge into health care practices, a process often referred to as implementation. The various subcultures that exist among health care workers may be an obstacle in this process. The aim of this study was to explore how professional groups and managers experienced the implementation of a new tool for lifestyle intervention in primary health care (PHC). The computer-based tool was introduced with the intention of facilitating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…no tailoring of activities to meet professional needs) was not successful in terms of uptake of the intervention. Beliefs, values and behaviours linked to professional subcultures influenced the implementation, and most professional groups found the intervention more suitable for other professionals, contributing to a low level of adherence [28]. Thus, adapting approaches to different subgroups, preferably by involving end-users, is a strategy to enhance the likelihood of success [6,8,10,22], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 84%
“…no tailoring of activities to meet professional needs) was not successful in terms of uptake of the intervention. Beliefs, values and behaviours linked to professional subcultures influenced the implementation, and most professional groups found the intervention more suitable for other professionals, contributing to a low level of adherence [28]. Thus, adapting approaches to different subgroups, preferably by involving end-users, is a strategy to enhance the likelihood of success [6,8,10,22], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 84%
“…One study found the information on one patient reported by a caregiver via an ICT to be insufficient , potentially impacting safety. This review also found that nurses believed that ICT could improve the quality and uniformity of care services . Additionally, nurses have reported that different ICT systems may improve accessibility and continuity of nurse care for patients .…”
Section: Resultsmentioning
confidence: 78%
“…However, one study found that the implementation of ICT in nursing practice led to fewer physical encounters with the patient . In fact, in several studies, nurses argued that ICT could not replace physical encounters with patients and that ICT had unfavourable effects on nurse–patient relationships . Some nurses view ICT as a threat to personal relationships and feel that no technological tools can replace face‐to‐face encounters or human touch .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding leadership, staff at all the units were confident that their manager was positive about staff discussing lifestyle issues with patients. When managers at the participating units were interviewed at the 9-month follow-up, they all seemed visionary about the implementation of the CLT, they perceived prevention as an important task, and felt a responsibility to provide preventive services [25]. Thus, both attitudes and leadership could have contributed to sustainability at all units.…”
Section: Discussionmentioning
confidence: 99%